Financial burdens and mental health needs in families of children with congenital heart disease. (6th April 2018) - McClung, Nancy; Glidewell, Jill; Farr, Sherry L.
Abstract: Objective: To examine the financial burdens and mental health needs of families of children with special healthcare needs (CSHCN) with congenital heart disease (CHD). Methods: Data from the 2009–2010 National Survey of Children with Special Health Care Needs (NS‐CSHCN) were used to examine parent‐reported financial burdens (out‐of‐pocket expenses, financial problems, employment impact, caregiving hours) and family members' need for mental health services in families of CSHCN with CHD. Multivariable logistic regression was used to compare financial burdens and family members' need for mental health services among CSHCN with and without CHD. Among CSHCN with CHD, multivariable logistic regression, stratified by age (0‐5 and 6–17 years), was used to assess characteristics associated with the outcomes. Results: Overall, families of 89.1% of CSHCN with CHD experienced at least one financial burden and 14.9% needed mental health services due to the child's condition. Compared with CSHCN without CHD, those with CHD had families with a higher prevalence of all financial burdens (adjusted prevalence ratio [aPR] range: 1.4–1.8) and similar family member need for mental health services (aPR = 1.3, 95% CI [1.0, 1.6]). Across both age groups, insurance type, activity limitations, and comorbidities were significantly associated with financial burdens and/or family members' need for mental health services. Conclusions: CSHCN with CHD, compared with those without CHD, lived in families with more financial burdens. Interventions that reduce financial burdens and improve mental health of family members are needed, especially among CSHCN with CHD who are uninsured and have comorbidities or activity limitations.